Aqueous Phase Synthesis of Hydrocarbons from Reactions of Guaiacol and Low Molecular Weight Oxygenates. Issue 22 (5th November 2018) - Agblevor, Foster A.; Jahromi, Hossein
Abstract: Catalytic pyrolysis of lignocellulosic biomass generates water‐soluble low molecular weight oxygenates such as acetic acid, acetone, furfural, butanone, guaiacol, phenol and others in significant quantities that will affect the profitability of the biorefinery process. A new heterogeneous catalyst has been developed that catalyzes the reaction of carbonyl compounds with unsaturated ethers in aqueous medium to produce C6 to C15 hydrocarbons in a one‐pot synthesis. These reactions are called "carbonyl alkylations" because the carbonyl carbon chain was added to the aromatic ring and the oxygen was eliminated without loss of carbon. The C1 to C4 ketones and aldehydes produce alkylated benzenes while the C5 and higher carbonyl compounds alkylated the benzene ring and also opened the benzene ring to produce long chain internal alkene compounds. All the reactions occurred in the aqueous media at 300–350 °C on a supported nickel catalyst. The gaseous products included low molecular weight hydrocarbons such as methane, propane, butane, and pentane. Thus, it has been demonstrated for the first time that it is possible to produce a wide array of hydrocarbons from low molecular weight biomass derived oxygenates. Abstract : Carbonyl alkylation : A novel supported Ni catalyst for the conversion of low molecular weight biomass pyrolysis oxygenates to long chain hydrocarbons through carbonyl alkylation reactions was developed. C1 to C4 carbonyl compounds react with anisole to produce alkylated benzenes while C5 and higher carbonyls produce linear and branched alkenes.